Direct immunofluorescence for the diagnosis of legionellosis - David JM Haldane; Ruth Peppard; Robert K Sumarah (Canadian Journal of Infectious Diseases)
Culture and direct immunofluorescent microscopy (DFA) results for Legionella pneumophila were reviewed over a two-year period. In the first year, a positive result was defined as having at least one morphologically typical fluorescing organism. In the second year, a positive was defined as at least five typical fluorescing organisms. Despite these stricter criteria and other measures to reduce the possibility of reagent contamination, there was no statistically significant difference in the sensitivity or specificity of the DFA in the two years for sputa, deep specimens or overall. Of 37 sputum specimens from infected patients, 16 were positive on DFA. Thirty-two of 38 positive patients were detected by sputum culture. DFA can provide rapid diagnostic information but cannot be used to rule out the diagnosis. Sputum is a useful specimen for the initial laboratory investigation of patients with legionellosis.